Empirical Rule of Stiction of Suction Cup - Mitsuo Matsuda (Japanese Society of Tribologists, 2008)
The purpose of this paper is to investigate stiction properties of suction cups on a flat surface and find out empirical rule of stiction. For this purpose, contact areas on SUS304 plate of three kinds (#40, 240, 400) of roughness under dry and wet contact conditions are made and pull-off test was carried. The SUS304 plate was fixed in the lower chuck of the tension tester, and the suction cup was chucked in the upper part of the tension tester. It is pushed by tension tester with initial compressive force Pc on the SUS304 plate, and then loaded by pulling force P at speed V=20 mm/min. In the whole pull-off process, the maximum pulling force (Pmax) and the final pull-off force (Poff) were observed. In conclusion, the empirical rule of stiction of suction cup : Pmax=σA, where Pmax[N], A [m2] and σ[Pa] are confirmed to exist, the σ is the constant depending on the roughness and dry or wet of plate surface.